Pengaruh Macroeconomi dan Bank Specific terhadap Non- Performing Loans pada Bank KBMI 3 yang Terdaftar di Bursa Efek Indonesia - Sastrawati , Tasya; Muchtar, Susi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the influence of internal banking factors as measured by the inflation rate, growth rate of gross domestic product, interest rate, bank size, return on assets, equity to assets, and credit growth on non-performing loans in the 13 conventional banks referred to in Bank Group According to Core Capital 3 listed on the Indonesia Stock Exchange (BEI) for 7 years (2015-2021). The data in this research are quantitative data obtained from the annual reports of banks included in the Bank Group based on Core Capital (KBMI) 3 in Indonesia which are available on the official website of the Indonesia Stock Exchange (www.idx.co.id), and the official website owned by each bank for 7 years (2021-2015).